PERANCANGAN MODEL PEMBELAJARAN PAI BERBASIS TEKNOLOGI DIGITAL - Eliva Sukma Cipta; Dendra Wijaya Daerobi; Eden Abdul Manan; Neng Astrilestari Putri; Wilda Solihat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the growing need for integrating digital technology in Islamic Education (PAI) learning models at the elementary school level. The research aims to design an effective digital-based PAI learning model that enhances student engagement, comprehension, and spiritual development while fostering 21st-century skills. This research employs a mixed-methods approach combining qualitative and quantitative data collection techniques. Data was gathered from 180 students, 45 teachers, and 30 parents through surveys, interviews, and classroom observations across five elementary schools in Bandung, West Java. The analysis reveals that digital-based PAI learning models incorporating interactive multimedia, gamification, and virtual classrooms significantly improve student learning outcomes. The implementation of this model demonstrates an average increase of 35% in student academic achievement and 42% improvement in spiritual development indicators. The study concludes that properly designed digital-based PAI learning models represent a viable and effective pedagogical strategy for contemporary elementary education. Future research should explore the long-term sustainability and scalability of these models across diverse socioeconomic contexts.